A New 4-Hydroxyisoflavanone from the Root of Oriental Tobacco and Their Antivirus Activities - Wu, Xianxue; Xu, Yong; Leng, Hongqiong; Yang, Guangyu; Chen, Yong-Kuan; Hu, Qiufen; Mingming, Miao (Asian Journal of Chemistry, 2013)
A new 4-hydroxyisoflavanone i.e., tobflavanone D (1), was isolated from the roots of oriental tobacco. Its structure was elucidated by spectroscopic methods, including extensive 1D and 2D NMR techniques. Tobflavanone D (1) was tested for their anti HIV-1 activities and anti-tobacco mosaic virus activities. The results showed that tobflavanone D (1) modest anti HIV-1 activities and antitobacco mosaic virus activities, respectively.